Evaluasi In Silico Interaksi Senyawa Bioaktif Daun Serai Cymbopogon citratus Terhadap Protein Sortase A Streptococcus mutans Sebagai Target Potensial Pencegahan Karies Gigi - Asmawati; Alfrida Monica Salasa; St. Ratnah; Sesilia Rante Pakadang; Muhammad Asman Setiawan Jumain; A. Moh. Whisnu Surya Dinata; Rizky Alfiana; Muh. Arfandy Gunawan (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Dental caries remains a major oral health problem with high prevalence and is primarily caused by the activity of Streptococcus mutans. One of the key virulence factors of this bacterium is Sortase A protein, which plays an essential role in bacterial adhesion and biofilm formation. This study aimed to evaluate the potential of bioactive compounds from Cymbopogon citratus as inhibitors of Sortase A from Streptococcus mutans using an in silico approach. The research method involved preparation of the Sortase A protein structure (PDB ID: 4TQX) and bioactive compounds of C. citratus, followed by molecular docking analysis using AutoDock Vina integrated with UCSF Chimera. Ligand–protein interaction analysis was performed to determine binding affinity and identify key amino acid residues involved, and the results were compared with a standard ligand (1QON). In addition, ADMET prediction was conducted to evaluate the absorption, distribution, metabolism, excretion, and toxicity profiles of the major compounds. The molecular docking results showed that luteolin and rutin exhibited strong binding affinities toward Sortase A, with binding energy values of -7.3 kcal/mol, comparable to the standard ligand (-7.2 kcal/mol). Luteolin demonstrated a similar interaction pattern with the standard ligand through the key residue Phe237, while rutin formed multiple hydrogen bonds around the active site. ADMET prediction indicated that luteolin possessed better oral absorption and a more favorable safety profile than rutin. In conclusion, luteolin is the most promising bioactive compound from Cymbopogon citratus for dental caries prevention through inhibition of Sortase A of Streptococcus mutans